2019
DOI: 10.14202/vetworld.2019.1013-1021
|View full text |Cite
|
Sign up to set email alerts
|

The role of edible bird's nest and mechanism of averting lead acetate toxicity effect on rat uterus

Abstract: Aim: This study aimed to evaluate the protective effect of edible bird's nest (EBN) supplement on the uteri of rats exposed to lead acetate (LA) toxicity. Materials and Methods: Five treatment groups were established as follows: Group 1 (C), which was given distilled water; Group 2 (T0), which was administered with LA (10 mg/kg body weight [BW]); and Groups 3 (T1), 4 (T2), and 5 (T3), which were given LA (10 mg/kg BW) plus graded concentrations of 30, 60, and 120 mg/kg BW of EBN, respectively, for days. Rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…In another in vitro study (with lead acetate), effects of lead on total antioxidant status (TAS) and activity of SOD in ovarian granulosa cells were observed [ 102 ]. Further research demonstrated that lead causes a significant reduction in gonadotropin binding, which altered the steroidogenic enzyme activity of granulosa cells [ 103 , 104 , 105 , 106 ].…”
Section: Lead (Pb)mentioning
confidence: 99%
“…In another in vitro study (with lead acetate), effects of lead on total antioxidant status (TAS) and activity of SOD in ovarian granulosa cells were observed [ 102 ]. Further research demonstrated that lead causes a significant reduction in gonadotropin binding, which altered the steroidogenic enzyme activity of granulosa cells [ 103 , 104 , 105 , 106 ].…”
Section: Lead (Pb)mentioning
confidence: 99%
“…The doses for EBN were chosen, according to Albishtue et al . ( Albishtue et al, 2019b ). The rat's BW was measured and recorded weekly in each group during the treatment period.…”
Section: Methodsmentioning
confidence: 99%
“…It had shown numerous medicinal benefits, such as enhancing the immune system, complexion & stimulating epidermal growth, inhibiting viral infections and apoptosis, improving respiratory and digestive problems ( Daud et al, 2019 , Haghani et al, 2016 ). Recent studies showed that EBN increased fertility rate and embryo implantation in rats exposed to lead acetate toxicity through a mechanism of enhancing the proliferation and differentiation of uterine structures (as demonstrated by steroid receptor expressions up-regulation) ( Albishtue et al, 2019b ). As of today, no prior studies on the role of EBN in Cd-mediated reproductive toxicity of female rats exist.…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial properties of EBN have also been proven through modern science and technology, revealing its nutritional values and pharmacological activities, including 1) body maintenance and enhancement of the immune system ( Marcone, 2005 ; Ma and Liu, 2012 ); 2) stimulation of cell growth ( Kong et al, 1987 ); 3) anti-inflammatory effect ( Vimala et al, 2012 ); 4) protection from joint degeneration and chondro-protection against osteoarthritis ( Matsukawa et al, 2011 ; Chua et al, 2013 ); 5) enhancement of antioxidant capacity-antioxidative effect ( Hu et al, 2016 ); 6) anti-influenza or as anti-viral agent ( Guo et al, 2006 ; Haghani et al, 2016 ; Hu et al, 2016 ); 7) skin whitening, anti-aging, anti-inflammatory and wound healing ( Zeng and Lai, 2019 ; Hwang et al, 2020 ); 8) promotion of corneal wound healing (eye caring) ( Zainal Abidin et al, 2011 ); 9) improvement of stem cell proliferation ( Roh et al, 2012 ); 10) learning and memory functions of multi-generational mice - ( Haghani et al, 2016 ; Careena et al, 2018 ; Xie et al, 2018 ; Khalid et al, 2019 ; Mahaq et al, 2020 ); 11) neuroprotection in Alzheimer’s or Parkinson’s disease ( Hou et al, 2017 ; Yew et al, 2018 ); 12) anti-obesity effects ( Yida et al, 2015 ); 13) prevention of cardio-metabolic and diabetic diseases ( Hou et al, 2015 ); 14) anti-hypertensive effect ( Ramachandran et al, 2018 ); and 15) amelioration of the detrimental effects of lead acetate (LA) toxicity in the uterus ( Albishtue et al, 2019 ). Therefore, EBN has proved its nutritional and therapeutic values.…”
Section: Introductionmentioning
confidence: 99%